LINC00520: A Potential Diagnostic and Prognostic Biomarker in Cancer - Zhang, Qiudan; Shen, Jinze; Wu, Yuchen; Ruan, Wenjing; Zhu, Feng; Duan, Shiwei (Frontiers in Immunology, 2022)
Long non-coding RNA (lncRNA) is important in the study of cancer mechanisms. LINC00520 is located on human chromosome 14q22.3 and is a highly conserved long non-coding RNA. LINC00520 is widely expressed in various tissues. The expression of LINC00520 is regulated by transcription factors such as Sp1, TFAP4, and STAT3. The high expression of LINC00520 is significantly related to the risk of 11 cancers. LINC00520 can competitively bind 10 miRNAs to promote tumor cell proliferation, invasion, and migration. In addition, LINC00520 is involved in the regulation of P13K/AKT and JAK/STAT signaling pathways. The expression of LINC00520 is significantly related to the clinicopathological characteristics and prognosis of tumor patients and is also related to the sensitivity of HNSCC to radiotherapy. Here, this article summarizes the abnormal expression pattern of LINC00520 in cancer and its potential molecular regulation mechanism and points out that LINC00520 can be used as a potential biomarker for cancer diagnosis, prognosis, and treatment.